Effects of Two Training Modalities on Body Fat and Insulin Resistance in Postmenopausal Women. Issue 11 (November 2017) - Henríquez, Sandra; Monsalves-Alvarez, Matías; Jimenez, Teresa; Barrera, Gladys; Hirsch, Sandra; de la Maza, María Pia; Leiva, Laura; Rodriguez, Juan Manuel; Silva, Claudio; Bunout, Daniel
Abstract : Abstract: Henríquez, S, Monsalves-Alvarez, M, Jimenez, T, Barrera, G, Hirsch, S, de la Maza, MP, Leiva, L, Rodriguez, JM, Silva, C, and Bunout, D. Effects of two training modalities on body fat and insulin resistance in postmenopausal women. J Strength Cond Res 31(11): 2955–2964, 2017—Our objective was to compare the effects of a low-load circuit resistance training protocol and usual aerobic training in postmenopausal women. Postmenopausal women with at least 1 feature of the metabolic syndrome were randomly allocated to a low-load circuit resistance training protocol or traditional aerobic training in a braked cycle ergometer. The intervention consisted in supervised sessions lasting 40 minutes, 3 times per week, during 6 months. At baseline and at the end of the intervention, fasting serum lipid levels, serum interleukin 6, C-reactive protein, 8 isoprostanes, and insulin resistance (assessed through QUICKI and HOMA-IR) were measured. Body fat was measured by double-beam X-ray absorptiometry and by computed tomography densitometric quantification at lumbar 3 vertebral level. Twenty-one women aged 58 (54–59) years were allocated to aerobic training and 21 women aged 55 (52–61) years were allocated to the low-load circuit resistance training protocol. Eighteen and 16 women in each group completed the 6 months training period. Women in both groups experienced significant reductions in blood pressure, total body, subcutaneous, and intraabdominal body fat. Reductions in total cholesterol and triacylglycerol levels were also observed. No changes in insulin resistance indexes, 8 isoprostanes, C-reactive protein, or interleukin 6 were observed in either group. No significant differences between treatment groups were observed in any of the measured parameters. We conclude that low-load circuit resistance training and aerobic training resulted in the same reductions in body fat and serum lipid levels.